2002
DOI: 10.1074/jbc.m109722200
|View full text |Cite
|
Sign up to set email alerts
|

Rice α-Amylase Transcriptional Enhancers Direct Multiple Mode Regulation of Promoters in Transgenic Rice

Abstract: Expression of ␣-amylase genes in cereals is induced by both gibberellin (GA) and sugar starvation. In a transient expression assay, a 105-bp sugar response sequence (SRS) in the promoter of a sugar starvation highly inducible rice ␣-amylase gene, ␣Amy3, was shown previously to confer sugar response and to enhance the activity of the rice Act1 promoter in rice protoplasts. A 230-bp SRS-like sequence was also found in the promoter of another sugar starvation highly inducible rice ␣-amylase gene, ␣Amy8. The ␣Amy8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 42 publications
4
45
0
1
Order By: Relevance
“…Embryo-specific sugar repression was further demonstrated by the fusion of a 230-bp aAmy8 promoter sequence with a reporter gene and an assay in transgenic rice seeds (Chen et al, 2002). In that study, aAmy8 promoter activity was repressed by sucrose in embryos but was insensitive to sucrose repression and activated by GA in endosperms.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Embryo-specific sugar repression was further demonstrated by the fusion of a 230-bp aAmy8 promoter sequence with a reporter gene and an assay in transgenic rice seeds (Chen et al, 2002). In that study, aAmy8 promoter activity was repressed by sucrose in embryos but was insensitive to sucrose repression and activated by GA in endosperms.…”
Section: Introductionmentioning
confidence: 92%
“…In rice and barley (Hordeum vulgare), the accumulation of a-amylase mRNA or protein is regulated negatively by sugars in embryos (Perata et al, 1997;Chen et al, 2002) and positively by GA in endosperms/aleurone cells Perata et al, 1997;Loreti et al, 2000). Embryo-specific sugar repression was further demonstrated by the fusion of a 230-bp aAmy8 promoter sequence with a reporter gene and an assay in transgenic rice seeds (Chen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid was introduced into Agrobacterium tumefaciens strain EHA101, and rice transformation was performed as described (Chen et al, 2002). Transformed calli were cultured in a liquid MS medium, containing 3% sucrose and 10 mM 2,4-D, for the establishment of suspension cell culture as described (Yu et al, 1991).…”
Section: Rice Transformationmentioning
confidence: 99%
“…11) It is now evident that the RAmy3B gene, which bears a gibberellin-response cis-element in the promoter region same as RAmy1A 12) and RAmy3E, 13) is dominantly expressed among the cluster genes at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Table 1, the expression products of RAmy1A, RAmy3B, and RAmy3E were major isoforms rice seeds germinating in 5 days. Chen et al (2002) 13) have recently demonstrated that mRNA of RAmy1A, RAmy1C, RAmy3B, and RAmy3E (Amy7, Amy10, Amy6, and Amy8) is actively expressed in the aleurone layer of 5-days germinated rice seeds. The similarity between RAmy1A and RAmy1C (Amy10) was approximately 91.5% at the N-terminal region (1 to 117), although the full protein sequence of RAmy1C is not opened yet.…”
Section: Discussionmentioning
confidence: 99%